Antiplasmodial activity and cytotoxicity of ethanol extract of Zea mays root - Jude Efiom Okokon; Bassey Sunday Antia; Bala Adamu Azare; Patience Jude Okokon (Mashhad University of Medical Sciences, 2017)
Objective:Zea mays root decoction that has been traditionally used for the treatment of malaria by various tribes in Nigeria, was evaluated for antimalarial potential against malaria parasites using in vivo and in vitro models. Materials and Methods: The root extract of Zea mays was investigated for antimalarial activity against Plasmodium berghei in mice using rodent malaria models; suppressive, prophylactic and curative tests and in vitro antiplasmodial activity against chloroquine-sensitive (Pf 3D7) and resistant (Pf INDO) strains of Plasmodium falciparum using SYBR green assay method. Median lethal dose and cytotoxic activity against HeLa and HEKS cells were assessed and phytochemical screening was also carried out using standard procedures. Results: The LD50 value of root extract was found to be 474.34 mg/kg. The crude extract (45-135 mg/kg, p.o) showed significant (p100 μg/ml against both HeLa and HEKS cell lines. Conclusion: These results suggest that the root extract of Zea mays possesses antimalarial activity against both chloroquine-sensitive and resistant malaria and these data justify its use in ethnomedicine to treat malaria infections.